The Influence of Husband’s Support on Baby Blues Syndrome among First-Time Mothers - Rini Indryawati; Salsa Khairun Nisa (Asosiasi Dosen Muda Indonesia, 2026)
The birth of a baby is a highly anticipated and meaningful event for married couples. However, empirical evidence indicates that approximately 57% of mothers in Indonesia experience baby blues syndrome, placing Indonesia among the countries with the highest prevalence of this condition in Asia. The significance of a husband's assistance in reducing postpartum emotional disorders is shown by this phenomenon. The purpose of this research was to look at first-time mothers and how much impact a spouse's support has on baby blues syndrome. Participating first-time postpartum mothers were the subjects of this quantitative study that used a purposive sampling method. A measure measuring husband support and the Edinburgh Postnatal Depression measure (EPDS) were used to gather data. With the help of Statistical Product and Service Solutions (SPSS) version 25 for Windows, we performed data analysis using basic linear regression. A correlation coefficient of R = -0.813 and a significant value of p = 0.000 (p < 0.05) showed that the husband's support had a highly significant impact on infant blues syndrome. These results show that first-time moms are less likely to experience baby blues syndrome if their husbands are more supportive. Women experience less emotional distress after giving birth to their first child when they have their husband's support.